Identification and “in silico” structural analysis of the glutamine-rich protein Qrp (YheA) in staphylococcus aureus (2019)
Background: YlbF and YmcA are two essential proteins for the formation of biofilm, sporulation, and competence in Bacillus subtilis. In these two proteins, a new protein domain called com_ylbF was recently discovered, but its role and protein function has not yet been established. Objective: In this study, we identified and performed an “in silico” structural analysis of the YheA protein, another com_ylbF-containing protein, in the opportunistic pathogen Staphylococcus aureus. Methods: The search of the yheA gene was performed using BLAST-P and tBLASn algorithms. The three-dimensional (3D) models of YheA, as well as YlbF and YmcA proteins, were built using the I-TASSER and Quark programs. The identification of the native YheA in Staphylococcus aureus was carried out through chromatography using the FPLC system. Results: We found that YheA protein is more widely distributed in Gram-positive bacteria than YlbF and YmcA. Two new and important characteristics for YheA and other com_ylbF-containing proteins were found: a highly conserved 3D structure and the presence of a putative conserved motif located in the central region of the domain, which could be involved in its function. Additionally, we established that Staphylococcus aureus expresses YheA protein in both planktonic growth and biofilm. Finally, we suggest renaming YheA as glutamine-rich protein (Qrp) in S. aureus. Conclusion: The Grp (YheA), YlbF, and YmcA proteins adopt a highly conserved three-dimensional structure, harboring a protein-specific putative motif within the com_ylbF domain, which possibly favors the interaction with their substrates. Finally, Staphylococcus aureus expresses the Grp (YheA) protein in both planktonic and biofilm growth.